Isolation, Characterisation and Antibiotic Susceptibility of Staphylococcal Isolates with Special Reference to Methicillin-Resistant Staphylococcus aureus From the Anterior Nares of Healthcare Workers in a Tertiary Healthcare Centre: S. aureus colonisation in healthcare workers - Chaurasia, Mukul; Agrawal, Neha; Chourasia, Ankita; Bhatnagar, Monica; Parihar, Geeta; Rastogi, Vijaylatha; Tak, Amit (Scripta Medica, 2021)
Background: Staphylococcus aureus (S. aureus) and its resistant form methicillin- resistant S. aureus (MRSA) is one of the most common nosocomial pathogens causing a wide range of infections in humans. The anterior nares are the main ecological niche for S. aureus. Nasal carriage of S. aureus acts as an important reservoir of infection among the colonised healthcare workers and they transmit the infection to the community. The aim of the present study was to estimate the nasal colonisation of S. aureus (with special reference to MRSA) in healthcare workers (doctors and nursing staff) and its antibiotic susceptibility pattern. Methods: A descriptive study was planned in the Department of Microbiology, JLN Medical College, Ajmer (Rajasthan, India) after due approval from the institutional ethics committee. A total of 170 healthcare workers of either sex aged between 18 to 60 years were screened for S. aureus. Identification was done using standard microbiological techniques, by studying their morphology, colony and biochemical characteristics. MRSA was detected by cefoxitin disc diffusion test, oxacillin disc diffusion test, minimum inhibitory concentration (MIC) of oxacillin by E-test and oxacillin screen agar test. The observations were described in proportions and Chi-squared test was used to find independence. Statistical significance was considered at 5 %. Results: Among 170 samples, 159 (93.53 %) samples (50 doctors and 109 nursing staff) had staphylococci colonisation. Among these 159 isolates, 34 (21.38 %) were S. aureus. Further, 8 (5.03 %) S. aureus isolates were resistant to both cefoxitin and oxacillin and had oxacillin MIC values ≥ 4 µg/mL and were considered MRSA. All the MRSA were detected in the nursing staff (males: 5.50 %, females: 1.83 %). All S. aureus and MRSA isolates were found sensitive to linezolid, vancomycin and mupirocin (minimum inhibitory concentration ≤ 4 µg/mL). Conclusion: Screening and treatment of healthcare workers colonised with MRSA should be an important component of hospital infection control policy. These measures will prevent spread of infection to patients and the community and thereby reduce the morbidity, mortality and healthcare costs associated with nosocomial infections.